2020
DOI: 10.26858/ja.v7i1.14777
|View full text |Cite
|
Sign up to set email alerts
|

The influence of work motivation, job satisfaction and work discipline on employee performance in the regional secretariat of Maros district

Abstract: This study aims to determine and analyze the influence of motivation, job satisfaction, and work discipline on employee performance at the Regional Secretariat of Maros Regency. This type of research is quantitative descriptive, while the nature of the research is descriptive explanatory research. The research was conducted at the Regional Secretariat of Maros Regency. The research was carried out for 3 months. The population in this study amounted to 96 employees at the Regional Secretariat of Maros Regency. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
(6 reference statements)
1
5
0
Order By: Relevance
“…This finding is in line with previous studies that satisfaction affected teacher work attitudes (Lee et al, 2017). After all, the condition of job satisfaction had a significant impact on leadership and teacher trust, how to work, happiness at work, and employee satisfaction (Andargie & Azar, 2019;Herman & Didin, 2020;Liu et al, 2020). This study is also findings, which concluded a relationship between teacher attitudes and job satisfaction (Saiti & Papadopoulos, 2015;Türkoğlu et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…This finding is in line with previous studies that satisfaction affected teacher work attitudes (Lee et al, 2017). After all, the condition of job satisfaction had a significant impact on leadership and teacher trust, how to work, happiness at work, and employee satisfaction (Andargie & Azar, 2019;Herman & Didin, 2020;Liu et al, 2020). This study is also findings, which concluded a relationship between teacher attitudes and job satisfaction (Saiti & Papadopoulos, 2015;Türkoğlu et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…Another problem that becomes a crucial factor is the motivation, interest, and job satisfaction offered by the industrial world (Herman & Didin, 2020). These aspects are very important to fulfill, so that interest in working in relevant industries will emerge from the graduates, which in turn will increase the number of graduates' absorption (Ollikainen & Karhunen, 2021;Stellmacher et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Even discipline becomes a part of a person's life, which appears in his daily behavior (Suyanto, 2018;Yuliandi & Tahir, 2019). Discipline occurs and is formed as a result and impact of a fairly long coaching process carried out from within the family and continues in education at school, because basically the family and school become an important place for the development of one's discipline (Herman & Didin, 2020;Hidayati et al, 2019). Furthermore Previous research added the function of discipline (Hu & Liu, 2020;Marzuki & Basariah, 2017).…”
Section: Discussionmentioning
confidence: 99%